Socio-economic profile and risk factors among pulmonary tuberculosis patients in Madurai, India: a cross sectional study - Mohamed, Saleem; Kanagasabapathy, Shankar; Kalifulla, Sabeetha (International Journal of Research in Medical Sciences, 2017)
Background: This study has been carried out to assess the socio-economic profile and underlying risk factors of pulmonary tuberculosis (PTB) patients registered under RNTCP programme of India and to find the differences based on their residential place. Methods: The study design was cross sectional consisting of 167 PTB patients from three DOTS centres in Madurai, Tamilnadu during August 2015. Data was collected using a questionnaire that included personal details, socio-economic and risk factors. Results: PTB was most prevalent in the age group of 35–54 years both in the urban (46.7%) and rural (49.4%) side. In the urban population, 67 (74.4%) were men whereas in the rural population they were 53 (68.8%). Maximum of the study subjects were from nuclear family (67.8% in urban and 89.6% in rural). About 20% of the patients studied were illiterates irrespective of their residential place. Labourers were 37% in urban area and 49% in rural area. Smoking, alcoholism and Diabetes Mellitus (DM) were more common among urban PTB patients while under-nutrition and poor housing among rural PTB patients. Conclusions: The study has concluded that the usual epidemiological pattern of PTB has been observed in both urban and rural setup as reported by other researchers. Socio-economic status and risk factors have played a vital role for treatment success. To eradicate Tuberculosis (TB), a holistic and interdisciplinary approach would be necessary to improve the socio-economic status along with proper screening and treatment of underlying risk factors. More precise health education and proper awareness programmes have to be implemented from the grass-root level to get rid of TB.